Narration in Ibn Qutayba’s book “Uyun - Hadeel Ali Kazem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The narration in Ibn Qutayba’s book (Oyoun Al-Akhbar) is marked by its modern storytelling style. The transmission of stories or anecdotal art excerpts or story excerpts that he quoted, he supplemented with his narrative self. As stated in the preface to his work, he combines it with reading pleasure and consistency to keep the reader from becoming bored. In his storytelling style, he incorporated the keys of a story, a contract, and a story plan, which were distinct from his time, and he approached the subsequent eras. As storytellers and narrators, they excelled throughout this period, particularly with Ibn Qutayba’s tales. This is what we describe to demonstrate the story’s manifestations and the author’s narrative style in reaching the peak, lowering to the solution, and then returning to a literary plot, in an artistic language, and drawing the lines between characters and dialogue DOI /10.54633/2333-021-042-014